1976
DOI: 10.1111/j.1365-2133.1976.tb02273.x
|View full text |Cite
|
Sign up to set email alerts
|

Measuring adrenal function in out-patients using topical corticosteroids

Abstract: A number of studies describing the effects on pituitary adrenal function of topically applied corticosteroids are reviewed. It is concluded that the adrenal function of the majority of out-patients is little affected by treatment with correctly prescribed topical corticosteroids. However, where patients need brief periods of treatment with large quantities of potent topical corticosteroids for extensive disease, clinicians should be aware of the possibility of transient adrenal suppression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

1978
1978
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…Two in dependent groups [1,5] concluded that adrenal suppression was likely to happen after 50 g/week or more of the cream or ointment formulations of clobetasol propionate were used in adults. This effect in different dosage has been seen for other corticosteroids [14,15], but, as Allenby et at. [1] observed, short-term adrenal suppression (as is also seen with short courses of oral prednisolone used to treat other conditions) is not a contra-indication for use, but one should be aware of it.…”
Section: Discussionmentioning
confidence: 84%
“…Two in dependent groups [1,5] concluded that adrenal suppression was likely to happen after 50 g/week or more of the cream or ointment formulations of clobetasol propionate were used in adults. This effect in different dosage has been seen for other corticosteroids [14,15], but, as Allenby et at. [1] observed, short-term adrenal suppression (as is also seen with short courses of oral prednisolone used to treat other conditions) is not a contra-indication for use, but one should be aware of it.…”
Section: Discussionmentioning
confidence: 84%
“…L'existence d'un parallélisme entre la dose de corticostéroïde appliquée localement et l'importance de la dépression surréna lienne est discutée. Cependant, celle-ci est bénigne si le traitement est de courte durée puisque les surrénales sont stimulables par le tétracosactide [5], comme nous l'avons constaté chez 10 de nos malades et même lorsque le taux de base du cortisol est effondré.…”
Section: Résultats Et Commentairesunclassified
“…Therapeutic response in early acute and sub-acute stages with corticosteroids could be excellent in prompt andadequate treatment is solicited. Occasionally, it will be necessary for patients with extensive disease to be treated with large quantities of the more potent preparations for a short time [2].…”
Section: Introductionmentioning
confidence: 99%